TRUST UNDER TRIAL: THE EFFECT OF SURGE PRICING ON TRUST TOWARD RIDE-HAILING PLATFORMS IN MANILA - Ramizo, Godofredo Jr (AoIR Selected Papers of Internet Research, 2019)
The nascent literature on platform trust in contexts of the Global South does not yet explain how trust for technology platforms persist or erode in the presence of issues that invite distrust, such as the controversial use of surge pricing in ride-hailing platforms. This paper uses in-depth interviews with 30 users of ride-hailing platforms in Manila to study how attitudes toward surge pricing influence attitudes for ride-hailing platforms. The paper finds that despite respondents’ negative attitudes toward surge pricing amid doubts on its fairness and transparency, trust for ride-hailing platforms persist. Persistence of trust is partly due to users’ rational experiences indicating that ride-hailing platforms provide net benefits despite the possibility of unfair surge pricing, especially when faced with the disagreeable alternative of using Manila’s poor transport infrastructure. However, the persistence of trust was also due to cognitive biases, as reflected in constructs such as _acceptance of limited transparency_, _perceived control_, and the ideational appeal of technological systems. These cognitive biases found in the data increase our understanding why trust in platform technologies may persist even when besieged by distrust. The findings can also increase our vigilance over the various cognitive biases which can be exploited to create trust on less than meritorious grounds, and hold a firm grip on users’ trust even as the latter begin to harbour healthy skepticism over fairness and transparency.